Law Enforcement Of Digital Asset Confiscation In Money Laundering Crimes - Tb. Soenmandjaja SD; Hono Sejati; Lamijan Lamijan (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
Money laundering is a serious crime that harms the interests of society, causes economic instability in a country, and is more dangerous than corruption because tracking the flow of money from money laundering will be more difficult. Due to this complexity, asset forfeiture becomes crucial because the approach method used is known as "follow the money." This research reviews asset forfeiture in money laundering from a law enforcement perspective. This research evaluates asset confiscation methods in money laundering cases from a law enforcement perspective, aiming to better protect societal interests and prevent criminals from gaining illicit profits. This research is normative or doctrinal, also known as dogmatic research with a conceptual and legislative approach. The findings indicate that, although asset forfeiture has been regulated through criminal prevention actions based on the Criminal Code and the Criminal Procedure Code, as well as civil and administrative actions based on the Anti-Money Laundering Act, there are still shortcomings in regulations that allow criminals to hide their illegal gains. It has not achieved justice and harms both the country and the victims of money laundering. To ensure crime doesn't benefit perpetrators, it's essential to expand asset seizure regulations by revising the Anti-Money Laundering Act to include civil seizures and cover all crime-related assets. Strengthening protections for innocent third parties is also necessary to uphold justice.